A history of pain trauma in modern Chinese literature and film - Berry, Michael 1974- (Global Chinese culture, 2011)
This work probes the restaging, representation, and reimagining of historical violence and atrocity in contemporary Chinese fiction, film, and popular culture. It examines five historical moments including the Musha Incident (1930) and the February 28 Incident (1947).